Zombie tapeworms in late capitalism: accelerating clinical and reproductive labour in Mira Grant's Parasitology Trilogy. Issue 4 (24th August 2016) - Attebery, Stina
Abstract : Biomedicine is increasingly shaped by the speculative economical values of neoliberal capitalism. A key feature of this new bioeconomical regime is the patenting and circulation of organisms and tissue samples, allowing rapid commercialisation of bacterial, animal and human biomedical materials. When thinking about this trend towards commercialisation, we must consider the ways by which biomedicine has been shaped by economics to better address these exploitative relationships between medical researchers and subjects. These fraught questions of agency and exploitation can be addressed through the concept of clinical labour, a term Melinda Cooper and Catherine Waldby coined to discuss embodied forms of labour, including surrogacy, clinical trials and tissue economies, that dominate the post-Fordist biomedical economy. As a genre that extrapolates from contemporary technoscientific practices, science fiction is uniquely positioned to explore the ethics of biomedical research in this neoliberal speculative economy. Science fiction can give human-like agency and affect to microbial, animal and alien life, allowing modified organisms to speak and interact with their creators. Creating these dialogues between commercialised organisms and biomedical researchers makes clear the connections between contemporary clinical practice and exploitative labour relations, illuminating the more troubling aspects of the new bioeconomy and imagining alternatives to this system.